Taeniophyllum rudolfii (Orchidaceae), a new species record for Thailand with a note on its typification - Chantanaorrapint, Sahut; Chantanaorrapint, Amonrat; Suddee, Somran (Thai Forest Bulletin (Botany), 2023)
Taeniophyllum rudolfii, previously known only from New Caledonia, was newly discovered in lower montane forest in southern Thailand. A description, line drawings and photographs are provided. In addition, a lectotype is also designated here.